Atypical presentation of a high-grade astrocytoma in a pediatric rheumatology Practice (One Health & Risk Management, 2020)
Introduction. Hip pain is common in childhood. The main dilemma is to differentiate between benign conditions and those causing significant morbidity and mortality.Material and methods. A clinical case report of a toddler presenting with Musculoskeletal (MSK) mask due to a brain tumor.Results. A 2-year-old boy presented to the ER complaining of hip pain, muscle weakness, and limping.  The neurologic exam showed no abnormalities. At the 3rd day of admission, patient condition worsened, and papillary edema was revealed. MRI revealed a tumor in the suprasellar cistern/prepons region.  Conclusions. In case of atypical MSK symptoms, a careful evaluation of children should be carried out to prevent any delay in diagnosis.
Keywords: astrocytoma; brain tumor; musculoskeletal mask; children.